Student to Scholar: Learning Experiences of International Students - Palmer, Yolanda Michelle (Journal of International Students, 2016)
The author discusses the learning experiences and processes of selected international graduate students within a Canadian university as they progressed from student to scholar. Inspired by social learning theorists Lave and Wenger’s (1991) notion of apprentice to masters in situated learning and communities of practice, the student to scholar framework sheds new light on the phenomenon of being an international graduate student. The arguments within the paper counter traditional views of learning as occurring solely through classroom engagements and offers that international graduate students learn and achieve “scholar” status through situated practice, professor mentoring and triple learning. Data were captured through observations and in-depth phenomenological and semistructured interviews.